Pengenkripsian dan Dekripsi Gambar Menggunakan Algoritma AES dengan MAC untuk Peningkatan Keamanan - Astawa, Ni Wayan Amanda Putri; Widiartha, I Made (Jurnal Nasional Teknologi Informasi dan Aplikasnya; Vol 1 No 3 (2023): JNATIA Vol. 1, No. 3, Mei 2023, 2023)
With the increasing importance of data security in digital image transmission and storage, this research presents an implementation of an image encryption and decryption program using the Advanced Encryption Standard (AES) algorithm combined with Message Authentication Code (MAC) for enhanced security. The program utilizes AES in CipherBlock Chaining (CBC) mode to ensure confidentiality and integrity of the image data. The unique key and initialization vector (IV) enhance the security of the encryption process. Additionally, the inclusion of MAC ensures data integrity and prevents unauthorized modifications during transmission or storage. The program offers a user-friendly web-based interface for easy usability. The implemented solution provides a high level of security for image data and can be applied in various applications requiring secure image transmission and storage. The effectiveness and reliability of the program are demonstrated through experimental results and evaluation.